Socioeconomic characteristics and constraints of participatory pond fish farmers in Mymensingh district, Bangladesh - Mithun, MNAS; Kowsari, MS; Sheheli, S (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study was conducted to determine the socioeconomic characteristics and constraints of participatory pond fish farmers in Muktagachha upazila (sub-district) under Mymensingh district of Bangladesh. Data were collected by using a structured interview schedule during 01 to 31 October 2018 from a sample of 100 fish farmers (50% of total population) who were selected randomly from a population of 200. Data were analyzed using descriptive statistics, rank order and coefficient of correlation. The majority of the participatory pond fish farmers (90%) faced medium to low constraints. Among 22 constraints, lack of training on aquaculture was identified as the most critical one, followed by high price of various inputs. The least important constraint of the farmers was crisis of water in dry season. It was revealed that fish farming experience, annual family income and training exposure were significantly associated with the constraints of participatory pond fish farmers. It is therefore recommended that the Department of Fisheries (DOF) and other related organizations can offer credit facilities, proper training and suitable extension services to minimize the constraints of participatory pond fish farmers and meet the increasing demand of fish in Bangladesh. Int. J. Agril. Res. Innov. Tech. 10(2): 170-176, December 2020